Interfaith Relations in Sundanese Society (A Study of the Tafsir Lenyepaneun by Moh. E. Hasim) - Chodijah, Siti; Anditasari, Putri (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
The purpose of this study is the construction of the interpretation of the Tafsir Lenyepaneun by Moh. E. Hasim in building interfaith relations in Sundanese society. This research method is qualitative with a character approach and his work. The results and discussion of this research include aspects of toleration in Islam (inter-religious relations), then the figure of the mufassir Moh. E. Hasim and the Tafsir Lenyepaneun and the verses related to tolerance of his interpretation. The conclusion of this research is that respecting and appreciating differences in beliefs is proof of faith in the God of Allah SWT. The mind given by God is used to establish peaceful and harmonious relationships, not to fight each other like animals.